Academic library paraprofessionals' role and job satisfaction - Gonda, Jojie A. (2006)
Library paraprofessionals are considered potential professional librarians, they should be given opportunities to grow and have a career path to improve their craft. The study examined the role and job satisfaction of academic library paraprofessionals in selected academic university in Metro Manila.